Nilai-nilai Moral dalam Novel Kasidah-kasidah Cinta Karya Muhammad Muhyidin - Novianti, Dina; Abdurahman, Abdurahman; Hamidin, Hamidin (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study were (1) to describe the morality worth in novel Kasidah-kasidah Cinta by Muhammad Muhyidin that corresponded by conscience, (2) to describe morality worth in novel Kasidah-kasidah Cinta by Muhammad Muhyidin that corresponded by endurance, (3) to deseribe the Kasidah-kasidah Cinta by Muhammad Muhyidin that corresponded by rights and responsibility, and (4) to describe the morality worth Kasidah-kasidah Cinta by Muhammad Muhyidin that corresponded by norm and worth. The results of this study were the morality worth in novel Kasidah-kasidah Cinta by Muhammad Muhyidin were the figure that have conscience, endurance, rights and responsibility, an norm and worth.